Remarks at the United Nations Secretary General’s International Ebola Recovery Conference, July 10, 2015 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses the dual challenge facing Guinea, Liberia, and Sierra Leone--that the Ebola epidemic stubbornly continues and that these countries must recover and build back better, stronger, and smarter. Ebola-affected countries need to dramatically increase access to essential, quality health care in even the most remote areas, and bolster the capacity of communities and community health workers to serve as the front line for disease prevention and response. He speaks about the need to strengthen the entire health system to achieve universal coverage and end preventable deaths. He talks about not letting up until we end this deadly epidemic once and for all and also must stand with the people of Guinea, Liberia, and Sierra Leone and make investments that produce a sustainable recovery. He concludes that as a global community, we must pledge to do whatever it takes to make sure such a preventable crisis never happens again.